Teaching English in an Inclusive Setting: An Investigation of Facilitating and Hindering Factors at Primary School - Rumenti Br Lumban Tobing; Made Hery Santosa; I Ketut Trika Adi Ana (Journal of Educational Study, 2026)
Inclusive education seeks to ensure equal learning opportunities for all students, including those with special needs, yet teaching English in inclusive classrooms presents specific pedagogical challenges. This study investigates the supporting and inhibiting factors in English teaching at SD N 2 Bengkala, North Bali, a school that integrates students with hearing impairments into regular classrooms. Employing a qualitative case study design, data were collected through classroom observations and in-depth interviews with the English teacher. The findings indicate that effective English instruction in this inclusive setting is supported by teacher adaptability, the use of visual media and concrete learning materials, assistance from special needs support teachers, peer support from regular students, and a positive classroom climate. However, several challenges persist, including communication barriers with deaf students, differences in learning abilities, emotional fluctuations, and environmental distractions. More complex English skills, such as listening, speaking, and writing, were found to be more difficult to teach than vocabulary. Overall, the study underscores the importance of adaptive teaching strategies and collaborative support in addressing learner diversity, while also highlighting ongoing challenges that require continuous adjustment to achieve inclusive English learning.